2018
DOI: 10.1016/j.jad.2018.02.070
|View full text |Cite
|
Sign up to set email alerts
|

affron®, a standardised extract from saffron (Crocus sativus L.) for the treatment of youth anxiety and depressive symptoms: A randomised, double-blind, placebo-controlled study

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in:Journal of Affective Disorders 232 (2018) However, this is the first study examining its mood-related effects in teenagers. MethodsIn this 8-week, randomised, double-blind, placebo-controlled study, youth aged 12 to 16 years, with mild-to-moderate anxiety or depressive symptoms were given tablets containing placebo or a saffron extract (affron ® , 14mg b.i. d). The youth and parent versions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 55 publications
0
38
0
6
Order By: Relevance
“…Effects of saffron on depressive symptoms. Randomeffects meta-analysis found a significant and large positive effect size for saffron reducing symptoms of depression in comparison with placebo (g ¼ 0.99, 95%CI ¼ 0.61-1.37, n ¼ 14 studies, n ¼ 716 participants, P < 0.001; Figure 2 [22][23][24][25][26][27][29][30][31][33][34][35][36][37][38][39][40]42,44 ). An additional study that could not be entered into the metaanalysis due to insufficient available data also found that saffron significantly improved depressive symptoms compared with placebo (P < 0.0001).…”
Section: Study Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of saffron on depressive symptoms. Randomeffects meta-analysis found a significant and large positive effect size for saffron reducing symptoms of depression in comparison with placebo (g ¼ 0.99, 95%CI ¼ 0.61-1.37, n ¼ 14 studies, n ¼ 716 participants, P < 0.001; Figure 2 [22][23][24][25][26][27][29][30][31][33][34][35][36][37][38][39][40]42,44 ). An additional study that could not be entered into the metaanalysis due to insufficient available data also found that saffron significantly improved depressive symptoms compared with placebo (P < 0.0001).…”
Section: Study Resultsmentioning
confidence: 99%
“…Most studies were conducted in Iran (n ¼ 21/23), with 2 studies conducted in Australia. 34,35 Thirteen studies were conducted by the same research group. Risk of bias across most studies was low, with 20 studies receiving a score of 4 or 5 (out of 5) on the Jadad Scale (see Appendix S2 in the Supporting Information online).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…e fast presence of crocetin in blood plasma after the administration of the saffron extract contributes to better explain saffron beneficial effects in animal models [48]. e commercial standardised saffron extract affron ® used in this study is related to beneficial effects in depression and mood disorders by several clinical trials at the dosage used in the present work [13,14,16] and in the reduction of inflammatory damage in the retina in an animal model of glaucoma [20]. e obtained results in this study increase the interest of saffron extract use as a new preventive therapy that requires a fast-active countereffect, for instance, as "fast-track" carotenoid in the Aged-Related Eye Disease Study (AREDS-2) formula.…”
Section: Discussionmentioning
confidence: 99%
“…e saffron (Crocus sativus L.) stigmas were extracted in the factory of Pharmactive Biotech Products S. L. in Madrid (Spain) to produce the commercial saffron extract, branded as affron ® , and dosed in tablets as preferred galenic form for the in vitro digestion and the clinical trial. Each tablet contained 14 mg of dried affron ® standardised to ≥3.5% lepticrosalides ® , defined as the content of bioactive compounds including safranal and crocin by HPLC [12,13], together with the following excipients: microcrystalline cellulose, calcium hydrogen phosphate, povidone, croscarmellose sodium, colloidal anhydrous silica, and magnesium stearate as excipients and coated with hypromellose (HPMC), macrogol (PEG) 8000, and carnauba wax.…”
Section: Materials and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation